(3Ndb CaYGd GdYHGOs - (3eMeO Hf ESeGYjd Hf EHQGgje GdLYaj GdHNGQj, CHh YHO Gddg , J (B256 (3g` s
(3ChdgG (B:s
(3jHOC HHGH eG PcQ Cgd GdYde ddeYWdI GdPjf jQjOhf Gf jHOdhG cdGe Gddg YR hLd s
(3BNQgG (B:s
(3Yf GHf YHGS bGd (B: (3cGf GdfHi Udi Gddg hSde EPG bGe Gddjd jJgLO jbhd Gddge dc GdMeO GfJ fhQ GdSehGJ hGdGQV hef ajgf hdc GdMeO GfJ bjhe GdSehGJ hGdGQV hef ajgf CfJ GdebOe hGfJ GdeDNQ dG Edg EdG GfJ (B) (3Je GdLR AGdKGfi HMeO Gddg hYhfg hMSf JhajbIs
(3HdZ ebGHdI hbQGAIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B52s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B722s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds